2018
DOI: 10.3390/molecules23061265
|View full text |Cite
|
Sign up to set email alerts
|

Whole Cells as Biocatalysts in Organic Transformations

Abstract: Currently, the power and usefulness of biocatalysis in organic synthesis is undeniable, mainly due to the very high enantiomeric excess reached using enzymes, in an attempt to emulate natural processes. However, the use of isolated enzymes has some significant drawbacks, the most important of which is cost. The use of whole cells has emerged as a useful strategy with several advantages over isolated enzymes; for this reason, modern research in this field is increasing, and various reports have been published r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 73 publications
0
45
0
Order By: Relevance
“…The high chemoselectivity in the bioreduction of chalcones observed in the present study is probably not due to the lack of ADH activity in the yeast strains, rather to the steric hindrance given by the bulky phenyl substituents or to enzyme localization (not accessible to the substrates). Anyway, the bioreduction of C=O bond in ketones bearing bulky substituents was found in bacteria whole cells [43], as well as in other microorganism [44][45][46][47] such as algae, filamentous fungi, yeasts and in plant tissues [48].…”
Section: Resultsmentioning
confidence: 99%
“…The high chemoselectivity in the bioreduction of chalcones observed in the present study is probably not due to the lack of ADH activity in the yeast strains, rather to the steric hindrance given by the bulky phenyl substituents or to enzyme localization (not accessible to the substrates). Anyway, the bioreduction of C=O bond in ketones bearing bulky substituents was found in bacteria whole cells [43], as well as in other microorganism [44][45][46][47] such as algae, filamentous fungi, yeasts and in plant tissues [48].…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes can be sourced from plants, e.g. carrots 10 and soy beans, 11 fungi 12,13 (such as baker's yeast, lamentous fungi and mushrooms), bacteria 14 and archaea. 15 The early use of readily available enzymes from animal organs, e.g.…”
Section: Sources and Commercial Availability Of Enzymes In The Metagementioning
confidence: 99%
“…In this case, only the S-enantiomer acts as a proton pump inhibitor and is used to treat gastric ulcers and gastroesophageal disorders. 3 Therefore, the stereoselective oxidation of organic suldes, the precursors for chiral sulfoxides, is receiving a growing interest nowadays. 4,5 Optically pure sulfoxides can be prepared via chemical or biological catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the use of whole cells, lysed cells, or cellular extracts as catalysts for asymmetric sulfoxidation reactions is a more attractive and a cheaper alternative since it avoids the need for adding expensive cofactors. 3 Fungi are widely used for catalyzing oxidation reactions compared to bacteria. [6][7][8] However, it was indicated that bacteria belonging to the genus Gordonia, Rhodococcus and Pseudomonas possess fairly high activity and enantioselectivity for a large number of suldes.…”
Section: Introductionmentioning
confidence: 99%